JUMPA Vol.4 No.2, Juni 2017 PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KOMPETENSI GURU TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI AKREDITASI “A” TIAP KELURAHAN DI KECAMATAN KEMAYORAN, JAKARTA PUSAT: PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KOMPETENSI GURU TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI AKREDITASI “A” TIAP KELURAHAN DI KECAMATAN KEMAYORAN, JAKARTA PUSAT - Akbar Widyaprabowo Sekolah Tinggi Ilmu Ekonomi Y.A.I; Desnirita Sekolah Tinggi Ilmu Ekonomi Y.A.I (Jurnal Manajemen dan Perbankan (JUMPA), 2017)
The teacher performance is a condition that inducates the result of work accomplished by a teacher in carrying out their duties and responsibilities in the school and describes the existence of an act that is displayed in the teacher of during learning activities. This study aims to determine how much the effect of the principal leadership and teacher competence both partial and together the teacher performance state elementary school accreditation of “A” each village in the subdistrict of Kemayoran, Central Jakarta.The method used in this research is descriptive, verifikatif and quantitative.Population amounted to 207 people. The results of this study prove partially principal leadership significant positive effect on the teacher performance, shown with regression coefficient of 0.673 and 10.449tcount>ttable1.988 and significant level sig. 0,000 ≤ 0.05. Teacher Competence significant positive effect on the teacher performance, as indicated by the regression coefficient of 0.681 and 11.675 tcount>ttable1.988 and significant level sig. 0,000 ≤ 0.05. And jointly principal leadership and teacher competence significant positive effect on teacher performance, indicated by 79.359Fcount>Ftable 3.10 and 0.000 ≤ 0.05 significance level,it is also supported with the value of R-square of 65.1%. This shows the magnitude of the contribution to principal leadership influencesand teacher competence on teacher performance of 65.1%.